El método triádico de Gérard Genette y análisis de la novela mañana volveré de Marcos Yauri Montero - Príncipe Cotillo, Guillermo (2022)
The main objective of the study was to apply the triadic method of Gérard Genette (1989), to analyze the narrative structure of the novel Tomorrow I will return. For this purpose, we started from the principle that every literary creation has two components: the story, represented by the what or level of meaning; and the discourse, the how or plane of the signifier. These components were analyzed taking into account the contributions of narratology and, assuming as a method of study, the three categories proposed by Genette: modalization, temporalization and spatialization. The results showed that the global corpus of the narrative has been built taking into account multiple points of view, called focalizations, added to distortions of time and the configuration of an extended socio-cultural space. This reality is heterogeneous, complex and contradictory, in which it coexists, especially the Andean migrant, in a marginalized condition and, worse still, uprooted, perhaps as a foreigner in his own country, symbolized in the figure of Raúl, the main character.